Xanthan biopolymer-based soil treatment effect on kaolinite clay fabric and structure using XRD analysis - Kwon, Yeong Man; Chang, Ilhan; Cho, Gye Chun (Scientific Reports, 2023)
In this study, we evaluated the impact of xanthan gum biopolymer (XG) on kaolinite fabrics using X-ray diffraction (XRD) and the ensuing changes in the compaction behavior and shear resistance of kaolinite soils. The XRD peak analysis revealed that XG changed kaolinite fabrics into face-to-face associations. Moreover, environmental scanning electron microscopy showed the formation of XG-bridges between kaolinite particles, resulting in the change in fabrics and subsequently improving the resistance of kaolinite to external forces. Consequently, as XG content increased, the maximum dry density decreased, and the undrained shear strength increased. The viscous XG hydrogels produced a higher optimal moisture content and increased resistance to shear force. This study showed that XG affects the mechanical properties of kaolinite through changing kaolinite fabrics (up to 0.5% of the XG-to-kaolinite mass ratio) and absorbing pore-fluids (excess XG over 0.5% of the XG-to-kaolinite mass ratio).